Database management system - Yadav, P. K. (New Delhi, India : S.K. Kataria & Sons, 2012)
This book dwells on fundamentals that one must learn in order to pursue virtually any endeavor in DBMS field. It trains student with the concepts needed to lay a Solid foundation for joining this exciting field. It is important to learn the fundamentals now so that one has the tools necessary to learn newer, emerging fields as they become more common. In simple words, reading this book will benefit anyone who wishes to arm themselves with substantive database skills.
1. Introduction to DBMS -- 2. Data Modeling Using the E-R Models -- 3. Relational Data Model and Language -- 4. Introduction to SQL -- 5. Normalization -- 6. Transaction Processing Concepts -- 7. Serializability and Deadlock Handling -- 8. Concurrency Control Techniques -- Index.
Includes index.
Keywords: DATABASE MANAGEMENT